Ascetic And Devotional Elements In The Mu‘tazilite Tradition: The Suf? Mu‘tazilites - Aydinli, Osman (The Muslim world, 2007)
Abstract: The Mutazilite thinkers are most often defined as rationalist, individualist, liberal and eccentric figures. To the above qualities, one should add ascetic and devotional aspects. Among the Mutazilite famous ascetics are Abū Mūsā al-Murdar and his followers, Ja‘far b. Harb, Ja‘far b. Mubashshir and ‘?sā b. al-Haytham. The accounts about these figures vigorously reflect the Mutazilite outlook of the ascetic life and practices. As a matter of fact, one can see the ascetic propensities in all the sects and schools of the early Islamic period. In view of their emphasis upon the love for God, they placed piety and austerity at the center of the relationship between the servant and God. In this context, this article attempts to provide insights into the pietistic dimension of the Mutazilite tradition.